Perbandingan antara Intervensi Koroner Perkutan dengan Bedah Pintas Koroner pada Unprotected Left Main Coronary Artery Disease di Pusat Jantung Nasional Harapan Kita - Jajang Sinardja; Yoga Yuniadi; Doni Firman (The Indonesian Heart Association, 2011)
Background. Despite many studies had been done comparing the outcome of Percutaneous Coronary Intervention (PCI) versus Coronary Artery By-pass Grafting (CABG) in Unprotected Left Main Coronary Artery Disease (ULMCAD), there is none such study in Indonesia.Aim. To compare the outcome of PCI versus CABG in ULMCAD patients at National Cardiovascular Centre Harapan Kita (NCCHK) Jakarta.Methods. A retrospective cohort study was done including 137 ULMCAD NCCHK patients who underwent PCI (n = 67) or CABG (n = 70) from July 2008 until March 2010. One-year Major Adverse Cardio Cerebrovascular Event (MACCE) outcome as defined by death, myocardial infarction (MI), stroke, and target vessel revascularization (TVR), were evaluated using Chi-square analysis, while Kaplan-Meier and Cox regression analysis were used to examine the survival curve of the mentioned intervention.Results. One-year risk of composite MACCE (death, stroke, and TVR) (hazard ratio (HR): 1.267; 95% confidence interval (CI): 0.567 – 2.829, p = 0.564), and the risk of death (HR: 1.080; 95% CI: 0.405 – 2.878, p = 0.878) were not significantly different for patients undergoing PCI versus CABG. Proportion of stroke was significantly higher in the CABG group (8.6% vs 0.0%; p = 0.014), while proportion of TVR was significantly higher in the PCI group (13.4% vs 0.0%; p = 0.001). No MI event was documented in both groups. Conclusion. During one-year follow up, PCI showed similar rate of composite MACCE and death, but higher TVR as compared to CABG in ULMCAD patients. Meanwhile CABG showed higher stroke rate as compare to PCI.